Benturan Peradaban dan Carut-Marut Postmodernisme - Zain, Muhammad (UIN Maulana Malik Ibrahim Malang, 2009)
The paper aims to view the Huntington's ideas from different perspective that is postmodernism. The writer assumes that Huntington's thesis is much easier to understand if it is placed on postmodernism discourse. The outstanding characteristics of postmodernism are decentralization, deconstruction, de-consensus, and